Phylogenetic relatedness determined between antibiotic resistance and 16S rRNA genes in actinobacteria - Ságová-Marečková, Markéta; Ulanova, Dana; Sanderova, Petra; Omelka, Marek; Kamenik, Zdenek; Olsovska, Jana; Kopecký, Jan (BMC microbiology, 2015)
BACKGROUND: Distribution and evolutionary history of resistance genes in environmental actinobacteria provide information on intensity of antibiosis and evolution of specific secondary metabolic pathways at a given site. To this day, actinobacteria producing biologically active compounds were isolated mostly from soil but only a limited range of soil environments were commonly sampled. Consequently, soil remains an unexplored environment in search for novel producers and related evolutionary questions. RESULTS: Ninety actinobacteria strains isolated at contrasting soil sites were characterized phylogenetically by 16S rRNA gene, for presence of erm and ABC transporter resistance genes and antibiotic production. An analogous analysis was performed in silico with 246 and 31 strains from Integrated Microbial Genomes (JGI_IMG) database selected by the presence of ABC transporter genes and erm genes, respectively. In the isolates, distances of erm gene sequences were significantly correlated to phylogenetic distances based on 16S rRNA genes, while ABC transporter gene distances were not. The phylogenetic distance of isolates was significantly correlated to soil pH and organic matter content of isolation sites. In the analysis of JGI_IMG datasets the correlation between phylogeny of resistance genes and the strain phylogeny based on 16S rRNA genes or five housekeeping genes was observed for both the erm genes and ABC transporter genes in both actinobacteria and streptomycetes. However, in the analysis of sequences from genomes where both resistance genes occurred together the correlation was observed for both ABC transporter and erm genes in actinobacteria but in streptomycetes only in the erm gene. CONCLUSIONS: The type of erm resistance gene sequences was influenced by linkage to 16S rRNA gene sequences and site characteristics. The phylogeny of ABC transporter gene was correlated to 16S rRNA genes mainly above the genus level. The results support the concept of new specific secondary metabolite scaffolds occurring more likely in taxonomically distant producers but suggest that the antibiotic selection of gene pools is also influenced by site conditions.
Keywords: ATP-Binding Cassette Transporters; ribozomální DNA; Genes, rRNA; DNA, Ribosomal; methyltransferasy; RNA, Ribosomal, 16S; shluková analýza; Molecular Sequence Data; ABC transportéry; Anti-Bacterial Agents; Methyltransferases; bakteriální léková rezistence; půdní mikrobiologie; Phylogeny; molekulární sekvence - údaje; Soil Microbiology; Sequence Analysis, DNA; Actinobacteria; geny rRNA; sekvenční analýza DNA; Cluster Analysis; antibakteriální látky; fylogeneze; Drug Resistance, Bacterial; RNA ribozomální 16S